2014
DOI: 10.1016/j.antiviral.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sheep pox virus vaccine for cattle against lumpy skin disease virus

Abstract: HighlightsKSGP O-240 strain was identified as lumpy skin disease virus.Commercially available KSGP O-240 vaccines should be re-characterized.The safety of these vaccines in cattle against LSDV should be re-evaluated.Two GTPV candidates were identified for use as a broad-spectrum capripox vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 35 publications
2
99
1
1
Order By: Relevance
“…All the samples were first tested using a general capripoxvirus (CaPV) real-time polymerase chain reaction (PCR) method (Bowden et al, 2008;Stubbs et al, 2012), followed by a CaPV species-specific PCR (Lamien et al, 2011a). The results were further confirmed using sequencing of the LSDV RNA polymer-ase subunit (RPO30) and the G-protein coupled chemokine receptor (GPCR) genes (Tuppurainen et al, 2014). In addition, histopathological examination was performed on a number of the tissue samples collected.…”
Section: Sample Analysismentioning
confidence: 99%
“…All the samples were first tested using a general capripoxvirus (CaPV) real-time polymerase chain reaction (PCR) method (Bowden et al, 2008;Stubbs et al, 2012), followed by a CaPV species-specific PCR (Lamien et al, 2011a). The results were further confirmed using sequencing of the LSDV RNA polymer-ase subunit (RPO30) and the G-protein coupled chemokine receptor (GPCR) genes (Tuppurainen et al, 2014). In addition, histopathological examination was performed on a number of the tissue samples collected.…”
Section: Sample Analysismentioning
confidence: 99%
“…In the scientific literature, adverse effects of vaccination with the live‐attenuated homologous vaccine (see footnotes 10, 11, 12, 13 at Section 3.2), such as local reactions at the vaccination site, generalised skin reactions in some vaccinated animals and decrease in milk yield have been reported in South Africa (Weiss, ; Hunter and Wallace, ). In addition, it has been reported that European dairy cattle may show adverse reactions after vaccination with the Kenyan sheep and goat pox (KSGP O‐240) vaccine in Africa (Yeruham et al., ; Kitching, ; Ayelet et al., ), which was likely associated with a low attenuation level of the vaccine, while the so‐called KSGP strain was later molecularly identified to be in fact a LSDV (Lamien et al., ,b; Tuppurainen et al., ). More recently, field veterinarians in Jordan reported a range of clinical signs seen after the administration of different capripoxvirus‐containing vaccines to prevent LSD infection in cattle (Abutarbush et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…RPO30 gene-based PCR depends on the presence of RPO30 gene encoding the 30 kDa RNA polymerase subunit in CaPVs [22-24]. Lamien et al .…”
Section: Introductionmentioning
confidence: 99%